Identification and validation of six acute myocardial infarction-associated variants, including a novel prognostic marker for cardiac mortality - Jeon, Yeonsu; Jeon, Sungwon; An, Kyungwhan; Kim, Yeo Jin; Kim, Byoung-Chul; Ryu, Hyojung; Choi, Whan-Hyuk; Choi, HyunJoo; Kim, Weon; Lee, Sang Yeub; Bae, Jang-Whan; Hwang, Jin-Yong; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Acute myocardial infarction (AMI) is one of the leading causes of death worldwide, and approximately half of AMI-related deaths occur before the affected individual reaches the hospital. The present study aimed to identify and validate genetic variants associated with AMI and their role as prognostic markers. Materials and methods: We conducted a replication study of 29 previously identified novel loci containing 85 genetic variants associated with early-onset AMI using a new independent set of 2,920 Koreans (88 patients with early- and 1,085 patients with late-onset AMI, who underwent percutaneous coronary intervention [PCI], and 1,747 healthy controls). Results: Of the 85 previously reported early-onset variants, six were confirmed in our genome-wide association study with a false discovery rate of less than 0.05. Notably, rs12639023, a cis-eQTL located in the intergenic region between LINC02005 and CNTN3, significantly increased longitudinal cardiac mortality and recurrent AMI. CNTN3 is known to play a role in altering vascular permeability. Another variant, rs78631167, located upstream of PLAUR and known to function in fibrinolysis, was moderately replicated in this study. By surveying the nearby genomic region around rs78631167, we identified a significant novel locus (rs8109584) located 13 bp downstream of rs78631167. The present study showed that six of the early-onset variants of AMI are applicable to both early- and late-onset cases. Conclusion: Our results confirm markers that can potentially be utilized to predict, screen, prevent, and treat candidate patients with AMI and highlight the potential of rs12639023 as a prognostic marker for cardiac mortality in AMI.